Phaonia magnicornis - Vikhrev, Nikita E.; Sorokina, Vera S. (Zenodo, 2017)
Phaonia magnicornis (Zetterstedt, 1845) Material examined. RUSSIA: Altai Republic : 1♂, Onguday env., 50.77°N 86.09°E, 840 m asl, 8– 13.07.2016, leg. N. Vikhrev (ZMUM). Distribution. Palaearctic, Nearctic: Alaska, Yukon. Published as part of Vikhrev, Nikita E. & Sorokina, Vera S., 2017, Taxonomic notes and faunistic data on the Muscidae (Diptera) of the Altai Mountains (Russia), pp. 241-254 in Zootaxa 4311 (2) on page 245, DOI:10.11646/zootaxa.4311.2.5, http://zenodo.org/record/847538